Peran Pemerintah Daerah dalam Pemeliharaan Bahasa Daerah Melalui Pendekatan Baru Revitalisasi Bahasa Daerah Model B di Kabupaten Nagan Raya - Sitompul, Siti Jahria; Syahputri, Veni Nella; Kesha, Cut Nabilla; Aduwina, Aduwina (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
The phenomenon of regional language extinction, particularly in Indonesia, is clearly evident and experienced by the language users themselves. In order to prevent the extinction of regional languages, the government has long established a legal framework for regional languages in Indonesia. The Minister of Education has also introduced guidelines (Models A and B) for the revitalization of local languages, with the aim of preserving them in Indonesia. These guidelines are intended to support local governments in adopting strategies to maintain and preserve local languages. Consequently, researchers have shown interest in examining the role of the Regional Government of Nagan Raya Regency in preserving the local language. This research employs a descriptive qualitative method, utilizing data collection techniques such as observation, documentation, and in-depth interviews. The findings of this research indicate that 5 out of 6 approaches to regional language revitalization efforts have been implemented in line with the Language Development and Development Agency (2022). However, the Nagan Raya government has not yet implemented an immersion-based learning approach to language revitalization, as this program is still unfamiliar to them. Nevertheless, other approaches, such as one-day language practice, technology-based learning, religion, arts and culture, and creativity, have been successfully implemented.